Physical aspects of matrix isolation technique: FTIR studies on CO and CO2 in O2 and N2 matrices: Low-Temperature Physics and Chemistry in Cryomatrice - Minenko, Maksym; Vetter, Martin; Brodyanski, Alexander P.; Jodl, Hans J. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2000)
The matrix isolation technique is traditionally used to investigate the properties of the matrix-isolated species themselves or to solve some special questions of the theory of defects in solid. We showed here that the optical spectroscopy of really matrix-isolated molecules can be successfully used to investigate the host crystal qualities too. We demonstrated the capacity of modern FTIR spectroscopy to study the properties of cryocrystals such as phase transitions, solubility boundaries, orientational order parameter, etc. by monitoring the behavior of the IR-active molecules, which are present in matrices under investigation as a natural contamination (40 ppb). Due to the excellent optical quality of our crystal samples, we were able to determine a part of the binary phase diagram CO-O2 (at CO concentrations less than 1 ppm) as well as to investigate the kinetics of phase transitions. Furthermore, we successfully used the spectroscopy of the matrix-isolated molecules to proof that the a-b phase transition of the matrix crystal (O2) is of first order.